If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -11 = a + 15 Reorder the terms: -11 + 3a = a + 15 Reorder the terms: -11 + 3a = 15 + a Solving -11 + 3a = 15 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -11 + 3a + -1a = 15 + a + -1a Combine like terms: 3a + -1a = 2a -11 + 2a = 15 + a + -1a Combine like terms: a + -1a = 0 -11 + 2a = 15 + 0 -11 + 2a = 15 Add '11' to each side of the equation. -11 + 11 + 2a = 15 + 11 Combine like terms: -11 + 11 = 0 0 + 2a = 15 + 11 2a = 15 + 11 Combine like terms: 15 + 11 = 26 2a = 26 Divide each side by '2'. a = 13 Simplifying a = 13
| x+100=500 | | 4+4x=48 | | c*(-19-(-27))=-160 | | x+x-3005=7815 | | -27-r=9 | | j*(-6)=330 | | j*(-6)=339 | | k+(-14)=-40 | | .13x+14.95=.39x-15 | | -7*n=175 | | -7*=175 | | 18955=8x+75 | | 6x+29=3x+71 | | x^9y^6/x^-3y^2 | | x^9y^6/x^-3y^2 | | -2*k=182 | | X^2+5x+0=0 | | -6-g=31 | | S/(-29)=-22 | | -40*c=560 | | -40*=560 | | 5x+1=180 | | -8+k=-11 | | -59-u=-26 | | 121-3x=24x+19 | | 1/3x+y=1 | | -42*(-21)=s | | 12x-4=-42+2 | | 3x-3=11x-65 | | 32/4+(3*7)*18+5 | | 10*3.14= | | 4x+6=-42-8 |